PEMODELAN DATA PROSES BISNIS PADA PERUSAHAAN ADVERTISING (STUDI KASUS CV ABC): DATABASE, CONTSTRAINT CHECK , PRIMARY KEY, FOREIGN KEY - Mutamassikin (FORTECH (Journal of Information Technology), 2020)
Database is a collection of information stored in a computer systematically so that it can be checked using a computer program to obtain information from the database, so that the database can help store data and information that can be retrieved at any time. The data and information that is owned by abc company consists of several, starting from ordering data, employee data, financial data, job distribution data, and information related to abc company. Database modeling in this case study uses a constraint check to provide a limit of the data inputted, so that later the data entered in the database table can be filtered that is not the same or in accordance with the constraint check that is inputted in the data table. The database capability to filter every existing data is one of the good and correct structures for implementing the constraint check in each database table, while the structures owned by the constraint check are primary key, foreign key, not null and uniqie. Therefore each structure has its own function, which will determine the level of accuracy of the data entered by the user, the better.